Serum Protein Profile Of Iraqi Hydatidosis Patients with Different Sites of Infection - Baghdad Science Journal (مجلة بغداد للعلوم)
Blood samples of One hundred and twenty patients from different hospitals in Baghdad infected with hydatidosis in different sites of the body (Liver, Lung, multiorgans and kidney) were collected for this study. On the other hand, 30 healthy individuals were included as a control group. This study was conducted to evaluate the effect of this disease on the serum protein profile of the patients using electrophoresis. The results revealed four different protein banding patterns with difference in number of bands and their molecular weights in comparison to the control group, and these differences depended on the site of infection. However the data showed a presence of the same band in all patients with different site of infection.